Post-nationalist American studies - Rowe, John Carlos (University of California Press, 2000)
Post-Nationalist American Studies seeks to revise the cultural nationalism and celebratory American exceptionalism that tended to dominate American studies in the Cold War era, adopting a less insular, more transnational approach to the subject.